Evaluation of Composition and Antioxidant Potential of Cordia macleodii - Adile, Sangeeta; Seth, Rohit (Journal of Biomedical and Pharmaceutical Research, 2024)
Cordia macleodii is one of the widely used traditional medicinal herbs. The current work was undertaken to systematically extract bioactive components from the fresh plant parts and evaluate their antioxidant potential. Using ethanol as the solvent, volatile chemical components were extracted from the plant material by Soxhlet extraction. Subsequently, GC-HR-MS and FTIR analysis were used to further evaluate the extract. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and 2,2’- Azinobis [3-ethylbenzothiazoline-6-sulfonic acid (ABTS)] were used to evaluate the antioxidant potentialof the extract in vitro. Quantification of total flavonoid content (TFC) and total phenolic content (TPC) was done against standard solutions of quercetin and gallic acid, which were used in the study as positive controls. The GC-HR-MS analysis reveals two bioactive compounds [(1H)- pyrrol-3-propanoic acid,2 ethoxy carbonyl-4-ethoxy carbonyl methyl]-5,5’-methylene, bis-diethyl ester and Spino [9,9’] difluorene,2,2’-[2,5,8,11-tetraoxado decane-1,12-diye). The FTIR spectrum showed that there were several different functional groups present. Findings of in vitroantioxidant tests revealed that the leaves had the highest total phenolic content (402.19 ± 0.025 mg GAE/g), the highest total phenolic content (93.59 ± 0.01), and the highest ABTS (102.59 ± 0.001) of any plant. To fully evaluate this plant’s therapeutic potential, more pharmacognostic research is required. Keywords: GC-HR-MS, FTIR, TPC, TFC, Antioxidant